Coexistence between Digital TV Broadcasting and Cellular Systems in UHF: Policy Implications - M. Abdelghany; F. Digham (International Telecommunications Society (ITS), 2019)
The World Radiocommunication Conference (WRC-15) decided to conduct a review of the spectrum usage in the 470-694 MHz frequency band at WRC-23 to study possible introduction of primary mobile service allocation in this frequency band that is currently utilized by Digital terrestrial TV broadcasting systems. Introducing new primary allocation for a service in a frequency band would require an examination of the coexistence between the new service and other incumbents. The frequency band 470-694 MHz is currently allocated to the broadcasting service on a primary basis in all three ITU regions and is used predominantly for the delivery of television broadcasting. In this case, it is required to assess the coexistence possibility between the incumbent broadcasting service (represented by DVB-T as digital TV system) and the new mobile service (represented by LTE as cellular system) in UHF below 694 MHz. The objective of this paper is to recommend a minimum frequency separation (guard band) between DVB-T and LTE based on a coexistence approach that promotes global spectrum harmonization in the 470-694 MHz frequency band, and to highlight the possible implications of this approach on the work of WRC-23 towards having a new co-primary mobile service allocation below 694 MHz in UHF.
Keywords: 330; Cellular-Broadcasting coexistence; Spectrum harmonization; UHF spectrum policy; Digital Dividend 3; WRC-23